Modified Extended Kumaraswamy Exponential Type-I Distribution on Environmental data - Yadav, Umesh Kumar; Kumar, Abhay (DEPAN, 2024)
This paper introduces a novel probability distribution, termed the Modified Extended Kumaraswamy Exponential Type-I Distribution (MEKWE), formulated by modifying the New Extended Kumaraswamy Exponential Distribution (NEKWE). The MEKWE distribution is characterized by its flexibility and ability to model data exhibiting various shapes such as skewness and kurtosis. The performance of the MEKWE distribution is evaluated using Maximum Likelihood Estimation (MLE) for parameter estimation and validated using real-world environmental data from Nepal (TSP of 2023). The distribution’s fit is assessed through various statistical tests, including the Kolmogrov-Smirnov (KS) test, AIC, BIC, and graphical diagnostics like histograms, box plots, and TTT plots. The MEKWE distribution outperforms other candidate distributions in terms of fitting the environmental data, demonstrating its potential application in environmental modeling, reliability engineering, and other fields requiring flexible modeling of lifetime data.